Global research trends of the studies on Murraya koenigii (L.) spreng: a Scopus-based comprehensive bibliometric investigation (1965–2023) - Siddig Ibrahim Abdelwahab; Manal Mohamed Elhassan Taha (Bulletin of the National Research Centre, 2023)
Abstract Background Murraya koenigii (L.) Spreng. has several well-established nutritional and therapeutic applications. Following our desire to investigate the global and scientific community's knowledge of medicinal plants, this study was intended to examine the evolution of knowledge related to M. Koenigii studies. The primary purpose of this paper is to clarify the status of these studies, investigate their methods, findings, and trends, and define their significance within the current research landscape. Results To achieve these goals, bibliometric analysis was conducted, retrieving, and analyzing 934 original articles published between 1965 and 2023 based on Scopus Dataset results. Data were exported as CVS (comma-separated values) and BibTex files and analyzed using Bibliometrix and VOSviewer software. Articles from 502 sources have been identified, averaging 21.8 citations per document. The research in this plant has had exponential growth (R 2 = 0.77). International co-authorship is 13.08%. India and Malaysia are the top publishing countries. Debajo, A.C. (Nigeria), Phatak,R.S. (India), and Sukari,M.A. (Malaysia) are the most productive authors. The top source is the Journal of Ethnopharmacology. "Green synthesis," "nanoparticles," "oxidative stress," "Asian citrus psyllid," "apoptosis," "antimicrobial," "anticancer," "Chromatographic profile," "bioactive compounds," and "alkaloids" are strongly related to the current trends in M. Koenigii research. Regarding the specialized topics, M. Koenigii's study concentrated on using this plant as an antioxidant agent in manufacturing and biological systems. Dynamic subjects like chromatographic profiles, essential oils, and Asian citrus psyllids were included in the motor theme. Conclusions The current study used bibliometric techniques to evaluate research on M. Koenigii and identify trends and potential future research hot spots.